Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


I don't know if this is correct or not but here goes.... By bringing 3a2 and 3a3 to rhs of equation, We have to prove that a4-a1=3a3-3a2 Lhs = a4-a1 = a+3d-a = 3d Rhs=3a3-3a2 = 3(a3-a2) = 3d Lhs=Rhs Thus proved(I think:))
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts